Applications of Cutting Stock Problem - Vladimir Medvid (Communications - Scientific letters of the University of Zilina, 2012)
We present one heuristic solution for the well-known cutting stock problem which was formulated by Kantorovich in 1939. It is the problem of filling an order at minimum cost for specified numbers of lengths of material to be cut to given stock lengths of given cost. When expressed as an integer programming problem the large number of variables involved generally makes computation infeasible. The same difficulty persists when only an approximate solution is being sought by linear programming.